#### Answer

-8$x^{2}$ + 10x

#### Work Step by Step

3(-4$x^{2}$ + 5x) - (5x - 4$x^{2}$)
Use the distributive property to remove the parentheses
=3.-4$x^{2}$ + 3.5x - (5x - 4$x^{2}$)
Drop parentheses and change the sign of each term in parentheses: - (5x - 4$x^{2}$) = - 5x + 4$x^{2}$
= 3.-4$x^{2}$ + 3.5x - 5x + 4$x^{2}$
Multiply
= -12$x^{2}$ + 15x - 5x + 4$x^{2}$
Group like terms
= (-12$x^{2}$ + 4$x^{2}$) + (15x - 5x)
combine like terms (-12$x^{2}$ + 4$x^{2}$) = (-12+4)$x^{2}$ = -8$x^{2}$, (15x - 5x) =(15 - 5)x = 10x
=-8$x^{2}$ + 10x